The Values Of Akhlaq Education In Surah Yusuf To Improve The Quality Of Islamic Religious Education: Nilai-Nilai Pendidikan Akhlak Dalam Surat Yusuf Untuk Meningkatkan Kualitas Pendidikan Agama Islam - Choirin, Besta Alby; Abdussalam, Aam; Surahman, Cucu (Civilization Research: Journal of Islamic Studies, 2024)
This study aims to determine the educational values in Surah Yusuf and its implications for PAI learning in schools. This research uses a qualitative approach assisted by tarbawy interpretation approach and maudhui (thematic) and muqaran (comparative) interpretation methods. The researcher becomes the key instrument in this research. The data sources used are the Qur'an and classical, modern, and contemporary tafsir books. Data collection techniques using literature studies (library research). Data analysis in this research includes data reduction, display, and verification activities. The values of moral education contained in Surah Yusuf are: First, the recommendation to love children. Second, the prohibition of having the nature of envy (hasan). Third, the prohibition of having a grudge. Fourth, the prohibition of lying (honest). Fifth, the recommendation maintain personal purity ('iffah). Sixth, the recommendation to hold fast to Allah SWT. Seventh, the recommendation to have patience. Eighth, the advice to maintain lust. Ninth, the advice to have an intelligent nature. Tenth, the recommendation to purify and magnify Allah SWT.